PHILOSOPHY EDUCATION IN THE PLEKHANOV RUSSIAN UNIVERSITY OF ECONOMICS (pages of history) - Aleksey I. Samsin (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
In February 2017 the Russian Plekhanov University of Economics celebrated its 110th anniversary. Establishment of the first Russian economics educational institution has its own history. It is closely connected with the period of complicated social and economic relations in the country and with conditions of the coming political and revolutionary events. From the very beginning not only applied subjects such as economics and product research, accounting, finance were taught but a wide range of theoretical social and humanitarian disciplines. The author analyzes the process of shaping a team of influential and experienced lecturers – professors, experts  in the field of philosophy and at the same time he highlights the work of the Philosophic Club of the Russian Plekhanov University of Economics.